Assessment of Satisfactions, Preferences, Needs and Use Patterns Quality Neighborhood Park Development in Malaysia - Abdul Malek, Nurhayati (2011)
The purpose of this study was to determine the quality aspects of neighborhood parks among Malaysian park users’. Hence, this research explores the causal relationship between, Quality green open spaces, Use patterns, Needs, Preferences and Overall satisfaction towards achieving a Quality Neighborhood Parks’ Criteria. A survey was administered to a sample of Malaysian neighborhood park users’. A total of 414 daily neighborhood park user responded to the survey. Structural equation modeling (SEM) technique was used to examine the hypothesized model of causal relationships among quality green open spaces variables, use of outdoor venues, preferences towards outdoor activities, needs in outdoor recreation as well as the overall satisfaction towards the neighborhood green open spaces using the AMOS 18 program. This study addresses the question of why does quality in green open spaces or Neighborhood Parks is needed? What are the evaluation criteria to determine the quality aspect of Neighborhood Parks?. The research argues that by integrating construct of quality green open spaces, use, preference, needs and satisfaction will help to assess better quality aspect of neighborhood parks. Results from the measurement model suggested that the model fit the data quite well. Results from the structural models identified several significant relationships among the latent structures. There is direct and significant relationship between use, needs and preferences aspect towards the quality of green open spaces. However, only use and needs aspect contributed to the overall satisfaction of park users with no direct effects towards quality green open spaces. Indicating insignificant relationships between satisfactions towards the quality of green open spaces. The result of the study also indicated that there was no significant correlation between gender, ethnic group, age group, marital status, monthly income, highest education level, and occupation type towards the quality of green open spaces aspect of the study. Hence, it could be summarized that the quality of a neighborhood park can only be achieved when use pattern, needs, preferences aspect are met. Omitting overall satisfactions as one of the factors in determining the success or quality of a neighborhood park.